EXAMINING JOB DEMANDS AS A MEDIATOR: UNRAVELING THE INFLUENCE OF ENTREPRENEURIAL ACTIVITIES ON JOB BURNOUT - Hardaningtyas , Ratna; Amin, Sirojuddin (Faculty of Economic and Business, University of Pasundan, 2024)
Given that burnout can have detrimental effects on both entrepreneurs and their businesses, it is crucial to comprehend how job demands affect burnout among entrepreneurs. Understanding the causes of burnout can help entrepreneurs manage their workload and resources more skillfully, which can improve both their personal and professional success. According to data from the Office of Cooperatives and Micro Businesses of Malang City, Indonesia, 126 respondents who were registered as